Differentially evolved glucosyltransferases determine natural variation of rice flavone accumulation and UV-tolerance. Issue 1 (December 2017) - Peng, Meng; Shahzad, Raheel; Gul, Ambreen; Subthain, Hizar; Shen, Shuangqian; Lei, Long; Zheng, Zhigang; Zhou, Junjie; Lu, Dandan; Wang, Shouchuang; Nishawy, Elsayed; Liu, Xianqing; et al.
Abstract Decoration of phytochemicals contributes to the majority of metabolic diversity in nature, whereas how this process alters the biological functions of their precursor molecules remains to be investigated. Flavones, an important yet overlooked subclass of flavonoids, are most commonly conjugated with sugar moieties by UDP-dependent glycosyltransferases (UGTs). Here, we report that the natural variation of rice flavones is mainly determined by OsUGT706D1 (flavone 7-O -glucosyltransferase) and OsUGT707A2 (flavone 5-O -glucosyltransferase). UV-B exposure and transgenic evaluation demonstrate that their allelic variation contributes to UV-B tolerance in nature. Biochemical characterization of over 40 flavonoid UGTs reveals their differential evolution in angiosperms. These combined data provide biochemical insight and genetic regulation into flavone biosynthesis and additionally suggest that adoption of the positive alleles of these genes into breeding programs will likely represent a potential strategy aimed at producing stress-tolerant plants. In contrast to flavonols, the functions of plant flavones are largely unknown. Here, the authors report the two differentially evolved glucosyltranferases (flavone 7-O -glucosyltransferase and flavone 5-O -glucosyltransferase) determine natural variation of rice flavone accumulation and UV-tolerance.